Hollow ceramic microspheres prepared by combining electro-spraying with non-solvent induced phase separation method: A promising feedstock for thermal barrier coatings. (5th February 2018) - Guo, Fangwei; Xing, Chen; Wang, Guowei; Zou, Zhonghua; Wang, Xin; Zhang, Qin; Zhao, Xiaofeng; Xiao, Ping
Abstract: Hollow microspheres were prepared by a combination method of electro-spraying and non-solvent induced phase separation, using a slurry of polymer with Y2 O3 -stabilized ZrO2 powder (YSZ). Subsequent sintering was carried out to obtain porous hollow YSZ microspheres with proper strength aiming to be thermal spraying feedstock. The ESNP particle size and distribution strongly depended on the applied voltage of the electro-spraying process and the jet nozzle diameter. The YSZ microspheres always consisted of a thin spongy shell and highly porous interior structure. The microsphere size decreased from 1000 to 100 μm with increasing voltage (10–20 kV). The cone-jet mode of electrospray reached steady as the nozzle diameter varied from 0.5 to 0.8 mm. Compared with the coatings made from commercial hollow spherical powder, the coatings prepared by ESNP powder had enhanced resistance to sintering and exhibited a longer life than commercial spray powder. It has demonstrated that the ESNP method provides a versatile way to manipulate the microstructure of ceramic microspheres, and could been used to fabricate high performance thermal barrier coatings by plasma spraying. Graphical abstract: Highlights: Porous hollow ceramic microspheres were prepared by combined electro-spraying and non-solvent induced phase separation. The microsphere size decreased from 1000 to 100 μm with increasing voltage (10–20 kV). The cone-jet mode of electrospray reached steady as the nozzle diameter varied from 0.5 to 0.8 mm. The microstructure of microspheres depends on the solvent amount and exchanging rate between the solvent and non-solvent. Coatings prepared using microspheres resist to sintering and exhibit a longer life than commercial powder.